(untitled) (Global Journal of Management and Business Research, 2012)
This study presents findings of in-depth interviews from #x2018;core-informants#x2019; from private sector organisations in Pakistan. Study identified that the impact of national cultural factors such as collectivism and high power distance have a strong influence on human resource management (HRM) practices and retaining competitive advantage at work. This study also revealed that sifarish (i.e. connection), sycophancy and nepotism are critical factors in HRM functioning. Typically organisations are hierarchically structured with unquestionable authority vested in either management or proprietor. The current investigation also found out that managerial support for sifarish or connection-based recruitment, selection and promotions practices are some of the main factors affecting to the development of HRM systems in private business sectors. Training and development practices are given little importance with absence of linkage between performance appraisal reward and promotions. The important implications for policy makers and heads of private organisations are discussed in the last section.